Praktikum za civilno procesno pravo - Rijavec, Vesna; Ivanc, Tjaša; Baghrizabehi, Denis (University of Maribor Press, 2020)
The Practicum for Civil Procedural law.The practicum is intended for law students and anyone who wants to test the importance of the rules of civil procedure with arguments from the most typical jurisprudence of Slovenian case law. Each carefully selected jurisprudence illustrates a particular important institute of civil procedural law.